A Convenient One-pot Synthesis of Chromenyl Acrylates and Acrylonitriles - Lopes, Diogo; Costa, Marta; Louçano, João; Proença, Fernanda (Synlett, 2020)
2H-Oxo-chromenyl acrylates and 2H-imino-chromenyl acrylonitriles have been prepared from a salicylaldehyde and ethyl cyanoacetate or 2-amino-1,1,3-tricyanopropene, respectively. The reaction occurs in the presence of 1,4-diazabicyclo[2.2.2]octane (DABCO) and the products were isolated in good to quantitative yields. Despite the simplicity of the synthesis, this is the first time that these substituted chromenes have been isolated.
Keywords: chromenyl-acrylate; chromenyl-acrylonitrile; salicylaldehyde; ethyl cyanoacetate; malononitrile